Climate justice at the local level: the case of Turkey - Sarıkoç Yıldırım, Beyza (My University, 2020)
Climate change is an issue of social justice, as it affects different social groups in the urban space differently. Yet, while formulating climate action plans, local governments often disregard the relationship between climate change and justice. By using content analysis, this article explores climate change action plans of Turkish municipalities from the perspective of climate justice. It concludes that action plans of Turkish municipalities do not consider climate change as a problem of justice despite the emerging or exacerbated inequalities in the urban space caused by climate change.
Keywords: Climate Change; Climate Justice; Local Governments; Municipalities; Urban Climate Justice